Spherical Bessel solutions of Maxwell’s equations in inhomogeneous rotationally symmetric media - Novitsky, Andrey V.; Rodriguez, Richard Jose Alvarez; Galynsky, Vladimir M. (Journal of the Belarusian State University. Physics, 2017)
Matrix approach applied earlier for description of electromagnetic waves in homogeneous rotationally symmetric media is generalized to inhomogeneous bianisotropic media. We propose the general method to determine material parameters of inhomogeneous media depending on the electromagnetic wave’s profile. We consider an inverse problem which is the search of the material tensors of inhomogeneous rotationally symmetric media with predetermined electric and magnetic wave’s fields in the form of spherical Bessel functions. Functioning of the approach is demonstrated with a particular example. The approach can be applied to create the required response of the artificial medium (metamaterial) on the external radiation.